Time series prediction of wind speed - Kalogirou, Soteris A.; Michaelides, Silas (My University, 2004)
In this paper a time series prediction of wind speed with artificial neural networks is presented. For this purpose the mean hourly wind speed records for the area of Kourris dam, located at the south of Cyprus, are used. Wind data for ten consecutive years (1991-2000) are available for this area. The network was trained to predict the mean monthly hourly wind speed of a year (e.g. 1994) by using the values of wind speed for the same month, same hour for the three previous years (e.g. 1991-1993), consecutively. The data for the wind speed up to the year 1999 have been used for the training of the network whereas those for the years 1997-1999 (input) and 2000 (output) were used for the validation of the network. It should be noted that the data for the year 2000 were completely unknown to the network. The wind speed for the validation data set was predicted with a correlation coefficient of 0.82 which is satisfactory for wind speed which is very unstable. Therefore the method proved to be very promising both for predicting missing values and for forecasting.
Keywords: Wind speed; Artificial neural networks